Theories and applications of plate analysis : - Szilard, Rudolph (John Wiley & Sons, Inc., 2004)
This book by a renowned structural engineer offers comprehensive coverage of both static and dynamic analysis of plate behavior, including classical, numerical, and engineering solutions. It contains more than 100 worked examples showing step by step how the various types of analysis are performed.